Designing and ERP System: A Sustainability Approach - Adriansyah, Aveicena Kemal; Ridwan, Ari Yanuar; Septo Hediyanto, Umar Yunan Kurnia (Society of Visual Informatics, 2022)
Technology has grown up massively, which is numerous aspects. Whether the system is limited or open source, had to adapt to certain circumstances. For instance, decades ago, people mainly used to have a paper to work on reporting or to make notes. These days, people started to migrate the work stuff into digitalization. Furthermore, environmental pollution has been triggered by emissions from vehicles. Moreover, due to a lack of knowledge and resources to solve this issue, the manufacturing process does not apply the sustainability process. This matter has led to an impenetrable environmental issue in the manufacturing area for years. Therefore, developing a sales module dashboard system that is configured on Sales Order (SO) transactions and customer data could assist the problem-solving process. The reason for this matter is to highlight the Key Performance Indicator (KPI) at the sustainability that has been added by the open-source Enterprise Resources Planning (ERP) System and display the indicator of data visualization application. Furthermore, the development of the ERP system is aligned with the purpose of the Quickstart methodology that was applied in this research. To sum up, the sales module dashboard system is designed to assist the new user in this implementation in classifying the material, process, or products that require consideration to be maintained.Â Moreover, to reduce the number of raw materials or shipment processes that did not apply the eco-friendliness